Analysis Of Effectiveness And Efficiency Of Utilization Of Aid Funds Health Operations (Bok) In South Kalimantan Province - Anggun Wulandari; Fauzie Rahman; Nur Laily; Nita Pujianti; Ayu Riana Sari; Lia Anggraini; Dian Rosadi; Abdul Thalib (International Journal of Medical Toxicology and Legal Medicine, 2024)
The Health Operational Assistance Fund (BOK) is used to assist Community Health Centers in implementing health service programs, but the average absorption valueBOK funds in 2019-2023 in Health center nationally have not been optimal. The purpose of this study isto analyze the effectiveness and efficiency of BOK implementation. The proposed method is analysis of policy through implementation research with a sequential explanatory approach.Data collection techniques were carried out by collecting secondary data, reviewing policy documents, focusing group discussions, and in-depth interviews. The selection of institutional samples used the stratified purposive sampling method. Based on the results of the study, it is known that BOK fund planning at the provincial and district levels follows technical instructions and national regulations. BPKAD and the Health Office face difficulties related to unit cost standards, as well as the lack of special BOK menus for mental health and the elderly at the Health center.The acceptance of BOK policy is going well, but the lack of financial human resources with adequate competence hampers management. BOK monitoring and evaluation at the provincial and district levels are running according to regulations, although reporting is sometimes not on time.The inconsistency of the initial disbursement schedule for funds at the Health Center and the large number of reporting applications burden human resources.